Hydrotherapy performance in elderly patients with herniated disk: a literature review (Research, Society and Development, 2018)
Disk herniation (DH) is a protrusion of the nucleus pulposus through the fibrous ring, arising because of trauma to the spine, which over time will damage the intervertebral discs. The objective of this work is to analyze the hydrotherapy effects on DH. It was done a descriptive analysis, with a bibliographic review on lumbar disc herniation, as well as its prevention measures, and developed and based on the analysis of scientific articles. Eleven articles were founded using the key-words disk herniation, physiotherapy and hydrotherapy on PubMed site. One of all obey to the inclusion propositions. In this way it concludes that the conservative treatment for lumbar disc herniation most indicated would be the hydrotherapy, because the physical properties of the water diminish the impact on the intervertebral discs due to the fluctuation causing a pain relief, thus providing a better quality of life to the patient.